Comparison of MRI Lesion Evolution in Different Central Nervous System Demyelinating Disorders. (14th September 2021) - Sechi, Elia; Krecke, Karl N.; Messina, Steven A.; Buciuc, Marina; Pittock, Sean J.; Chen, John J.; Weinshenker, Brian G.; Lopez-Chiriboga, A. Sebastian; Lucchinetti, Claudia F.; Zalewski, Nicholas L.; Tillema, Jan Mendelt; Kunchok, Amy; et al.
Abstract : Background and Objective: There are few studies comparing lesion evolution across different CNS demyelinating diseases, yet knowledge of this may be important for diagnosis and understanding differences in disease pathogenesis. We sought to compare MRI T2 lesion evolution in myelin oligodendrocyte glycoprotein immunoglobulin G (IgG)–associated disorder (MOGAD), aquaporin 4 IgG–positive neuromyelitis optica spectrum disorder (AQP4-IgG-NMOSD), and multiple sclerosis (MS). Methods: In this descriptive study, we retrospectively identified Mayo Clinic patients with MOGAD, AQP4-IgG-NMOSD, or MS and (1) brain or myelitis attack; (2) available attack MRI within 6 weeks; and (3) follow-up MRI beyond 6 months without interval relapses in that region. Two neurologists identified the symptomatic or largest T2 lesion for each patient (index lesion). MRIs were then independently reviewed by 2 neuroradiologists blinded to diagnosis to determine resolution of T2 lesions by consensus. The index T2 lesion area was manually outlined acutely and at follow-up to assess variation in size. Results: We included 156 patients (MOGAD, 38; AQP4-IgG-NMOSD, 51; MS, 67) with 172 attacks (brain, 81; myelitis, 91). The age (median [range]) differed between MOGAD (25 [2–74]), AQP4-IgG-NMOSD (53 [10–78]), and MS (37 [16–61]) ( p < 0.01) and female sex predominated in the AQP4-IgG-NMOSD (41/51 [80%]) and MS (51/67 [76%]) groups but not among those with MOGAD (17/38 [45%]). Complete resolution of the index T2 lesion was more frequent in MOGAD (brain, 13/18 [72%]; spine, 22/28 [79%]) than AQP4-IgG-NMOSD (brain, 3/21 [14%]; spine, 0/34 [0%]) and MS (brain, 7/42 [17%]; spine, 0/29 [0%]) ( p < 0.001). Resolution of all T2 lesions occurred most often in MOGAD (brain, 7/18 [39%]; spine, 22/28 [79%]) than AQP4-IgG-NMOSD (brain, 2/21 [10%]; spine, 0/34 [0%]) and MS (brain, 2/42 [5%]; spine, 0/29 [0%]) ( p < 0.01). There was a larger median (range) reduction in T2 lesion area in mm 2 on follow-up axial brain MRI with MOGAD (213 [55–873]) than AQP4-IgG-NMOSD (104 [0.7–597]) ( p = 0.02) and MS (36 [0–506]) ( p < 0.001) and the reductions in size on sagittal spine MRI follow-up in MOGAD (262 [0–888]) and AQP4-IgG-NMOSD (309 [0–1885]) were similar ( p = 0.4) and greater than in MS (23 [0–152]) ( p < 0.001). Discussion: The MRI T2 lesions in MOGAD resolve completely more often than in AQP4-IgG-NMOSD and MS. This has implications for diagnosis, monitoring disease activity, and clinical trial design, while also providing insight into pathogenesis of CNS demyelinating diseases.